Exploring the Use of YouTube Media in Islamic Religious Education Learning in the Digital Era - Wa Ode Yani; Aris Tanto; Dulham (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study explores the effectiveness of utilizing YouTube as an instructional medium in Islamic Religious Education (PAI) for fourth-grade students at SDN 1 Nganganaumala, Baubau City. In the context of digital learning, YouTube offers visual and contextual representations that support students' comprehension of abstract religious concepts. Using a qualitative descriptive approach, data were collected through interviews and documentation with PAI teachers. The findings reveal that YouTube significantly enhances student engagement, promotes better understanding of religious values, and encourages both independent and collaborative learning among students. Moreover, the study identifies several challenges, including limited access to digital infrastructure, dependency on stable internet connections, and the need for content curation to align with Islamic educational values. Despite these obstacles, YouTube presents meaningful opportunities for teachers to innovate and adapt their instructional strategies in accordance with 21st-century learning demands. The study contributes to the growing body of literature on digital media integration in religious education and underscores the importance of media literacy training and supportive policy frameworks to maximize its educational benefits. Future research is recommended to explore long-term impacts and develop best practice models for digital learning in Islamic education.